COLLABORATION-BASED PUBLIC SERVICES: THE ROLE OF THE SURABAYA CITY CIVIL SERVICE POLICE UNIT AND LOCAL STAKESHOLDERS IN SUKOLILO DISTRICT - Arif Fitriansyah , Dimas; Roekminiati, Sri; Devy pramudiana, Ika; Pramono , Sapto (International Journal of Multidisciplinary Reseach, 2025)
This research examines cooperative public service practices involving the Municipal Police (Satpol PP) of Surabaya City and local stakeholders in the Sukolilo District, emphasizing the mapping of the collaboration network, evaluating coordination mechanisms, and identifying challenges and effective strategies that can enhance the execution of local policies. Employing a descriptive qualitative method, data were gathered via in-depth interviews, participatory observations, and document analysis, then analyzed through thematic analysis to uncover interaction patterns, role allocation, and collaborative governance dynamics at the community level. The results indicate that the collaboration network includes governmental bodies, community leaders, local units, business representatives, and security organizations, though the level of interaction and frequency differ by region. Coordination mechanisms function via official platforms and online communication channels; however, issues remain, such as overlapping authorities, uneven information distribution, and restricted human resources. Notwithstanding these challenges, a number of best practices arise, including the utilization of digital communication tools for swift responses, engagement of community leaders in resolving conflicts, and the implementation of collaborative enforcement strategies. The research highlights the necessity to bolster collaborative governance frameworks, improve cross-sectoral capacity development, and standardize coordination methods to enhance the efficiency of public service delivery. This study enhances collaborative governance frameworks in urban settings and provides policy suggestions to strengthen partnership-driven public services.